What If All Value Were Conferred?. (13th October 2017) - Soto, Carlos
Abstract : I argue that the claim that all value is conferred is incompatible with the view that the capacity to set ends is unconditionally valuable. While this objection has been made, I offer a rebuttal and then a counterexample to the rebuttal. I also argue that, if all value were conferred, then the Kantian notion that moral wrongness consists in a practical contradiction is undermined.